Karakteristik Pendidikan Dasar (SD dan SMP) di Kota Kupang Provinsi Nusa Tenggara Timur - Budi Koestoro (Universitas Negeri Yogyakarta, 2007)
This research intended to appreciate the facts of (1) School climate for basic education, (2) society participation on the basic education, (3) Leadership of the school on basic education, ( 4) Input of the school for basic education, ( 5) teaching and learning process which school carried out for basic education, and ( 6) Image of the school that execute basic education. The ex post facto method was conducted in this research. Research population are education stakeholder at set of education of SD and SMP. The sample was determined with cluster random sampling technique. Questionnaire, guidance of interview, and documentation was conducted to get data and quantitative analysis with descriptive statistic and enriched with qualitative analysis. Result of the research indicate that (1) School climate that execute basic education in Kota Kupang of Nusa Tenggara Timur Province have goodness or conducive condition. Generally, the schools have serious efforts to create and improve school climate which progressively. (2) Degree of student parent participation or society participation is not yet optimal that is residing at good condition (the ground of good position) so that admit to be improved. (3) Generally, The school have very good leadership pattern that is good sociability of teachers to school citizen, teachers have democratic model in teaching and learning process, and the teachers have the best set an example for his/her students or school citizen. (4) Condition of facilities and basic facilities that found in the schools as basic education organizer generally have a goodness condition, treatment of facilities and basic facilities was happened as weakness that relate to those facilities, so the facilities and basic facilities not optimally function yet. (5) Input for the Elementary School and Junior High School generally reside in good category. (6) Teaching and learning condition at the schools that organized of basic education have a good category. This means, that the teacher have ability to listen the student complaint, teaching method that applied the teacher can improve students being active in the teaching and learning process, good class atmosphere in the teaching and learning process, and very conducive for using optimally teaching aid in the teaching and learning process. (7) interscholastic as an organizer of basic education to improve quality and development of school program have a tight or high competitive category.